Cone-beam CT reconstruction for planar object - Liu, Tong (NDT & E international : independent nondestructive testing and evaluation, 2012)
All traditional CT reconstruction algorithms define the reconstruction slices as perpendicular to the axis of rotation. This leads to a significant inefficiency when reconstructing and visualizing multilayered planar objects such as stacked IC and MEMS devices. This paper reports an alternative solution to the planar CT reconstruction technologies that are published previously, based on a modified version of the widely used FDK cone-beam reconstruction algorithm. The present method distinguishes itself to the existing planar CT technologies and all other traditional CT reconstructions by defining the reconstruction slices along the exact orientation of the planar object in the scan. This new method still possesses the advantages of the previous planar CT technologies such as efficient reconstruction in terms of computation time and resources saving, higher reconstruction resolution in preferred direction, easy visualization, and so on. But it also has better performance than the existing ones by providing an analytical solution to the low-efficiency problem of the traditional FDK algorithm, further reducing the reconstruction volume, and eliminating the interpolation error induced by an image rotation process that is required by the previous planar CT methods.